A criss-cross of forces: The power relationship in the process of creating the citizenship curriculum in Taiwan - Cheng-Yu Hung (Informascope, 2019)
The citizenship curriculum used in Taiwan during the authoritarian period from 1949 to 1987 sacrificed the individual for the national interest as a tool for political socialisation. In the wake of democratisation since 1987, the curriculum has gradually been stripped of its nationalist overtones which were designed to foster 'informed citizens' to facilitate those in power. The increased stress on the reflective and critical capabilities of the individual reminds pupils to examine their positions and roles in society instead of mechanistically accepting the existing social structure. This article sheds light on the intricate internal-external power relationships and differing views on critical pedagogy among curriculum designers. Interviewed curriculum designers hold that pluralistic ideologies should be presented in the curriculum and then room should be left for students to deliberate or judge for themselves. As the gatekeepers tasked with deciding which information to include and being faced with the intervention of numerous internal and external forces, the Curriculum Committee sided with the critical theory and aimed to break the unreflective social reproduction. Keywords: Curriculum Studies, Citizenship Education, Critical theory, Critical Pedagogy, Curriculum Design, and Social Reproduction